2008
DOI: 10.1186/1471-2431-8-30
|View full text |Cite
|
Sign up to set email alerts
|

A puzzle form of a non-verbal intelligence test gives significantly higher performance measures in children with severe intellectual disability

Abstract: Background: Assessment of 'potential intellectual ability' of children with severe intellectual disability (ID) is limited, as current tests designed for normal children do not maintain their interest. Thus a manual puzzle version of the Raven's Coloured Progressive Matrices (RCPM) was devised to appeal to the attentional and sensory preferences and language limitations of children with ID. It was hypothesized that performance on the book and manual puzzle forms would not differ for typically developing childr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
12
0
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 31 publications
1
12
0
4
Order By: Relevance
“…While all Raven versions minimize both the need for instructions and demands for specific abilities (for example, typical language comprehension or production), RCPM board form enhances this Raven feature and, further, eliminates any requirement to point. There is preliminary evidence [ 18 ] that an improvised board or ‘puzzle’ form of RCPM, while equivalent to the on-paper version in typical children, produces both better scores and a higher completion rate in school-aged autistic children labeled with severe intellectual disability. A published large data set including RCPM board form scores for 256 autistic children aged 7 to 11 years [ 19 ] also suggests this test belongs in a strength-informed assessment for minimally verbal autistic children in this age range.…”
Section: Introductionmentioning
confidence: 99%
“…While all Raven versions minimize both the need for instructions and demands for specific abilities (for example, typical language comprehension or production), RCPM board form enhances this Raven feature and, further, eliminates any requirement to point. There is preliminary evidence [ 18 ] that an improvised board or ‘puzzle’ form of RCPM, while equivalent to the on-paper version in typical children, produces both better scores and a higher completion rate in school-aged autistic children labeled with severe intellectual disability. A published large data set including RCPM board form scores for 256 autistic children aged 7 to 11 years [ 19 ] also suggests this test belongs in a strength-informed assessment for minimally verbal autistic children in this age range.…”
Section: Introductionmentioning
confidence: 99%
“…Six possible pieces are displayed as alternatives to best complete the pattern. The puzzle version (Bello et al, 2008 ) was used in the current study as it has been shown to reliably measure non-verbal mentation of individuals equal to the standard book form in children with typical development (Bello et al, 2008 ), and to increase response rate of children with ID. The puzzle version of RCPM uses identical matrices to the book form, but the six alternative answers are attached by Velcro requiring the participant to actually replace and reattach the chosen/preferred answer.…”
Section: Methodsmentioning
confidence: 99%
“…Individuals with ASD exhibit relatively high performance on the Block Design task even as general IQ decreases (Lincoln et al, 1988 ; Allen et al, 1991 ; Venter et al, 1992 ; Shah and Frith, 1993 ; Happe, 1994 ; Muth et al, 2014 ). Furthermore, while language based subtests are predictive of general IQ in typically developing populations, this is not considered to be the case for ASD (Bello et al, 2008 ; Charman et al, 2011 ; Muth et al, 2014 ; Courchesne et al, 2015 ). Similar comment on the pattern of strengths and weaknesses of visual processing associated with intelligence in ASD is limited due to the predominant use of the ASD without-ID population (see Muth et al, 2014 for comment).…”
mentioning
confidence: 99%